Effect of internal hydrocarbon reforming during coupled operation of a biomass gasifier with hot gas cleaning and SOFC stacks. Issue 4 (22nd April 2019) - Fischer, Felix; Hauser, Michael; Hauck, Maximilian; Herrmann, Stephan; Fendt, Sebastian; Jeong, Hyeondeok; Lenser, Christian; Menzler, Norbert H.; Spliethoff, Hartmut
Abstract: In the context of energy transition and climate change, a combination of highly efficient modern solid oxide fuel cells (SOFC) and thermo‐chemical conversion of biogenic residues could complement other intermittent renewable sources such as wind and solar. In order to reduce required gas cleaning efforts and to increase the process efficiency, the influence of hydrocarbons on SOFC performance is experimentally investigated in this study. For the first time, the operation of Ni/YSZ anode‐supported cells in Jülich F10 stacks is performed with pre‐reformed and with bio‐syngas containing full hydrocarbon content at realistic current densities. Sulfur and other impurities were removed in both cases. No degradation could be observed within normal operation on clean gas. With the tar reformer bypassed, the pressure drop over the stack increased due to severe carbon deposition on the anode substrate and the nickel current collector mesh inside the SOFC stack, so that operation had to be terminated after five hours. This behavior is different from single‐cell tests, where electrochemical degradation is the limiting factor. The results show that improvements are not only necessary for cell materials and that future research must also consider other stack components. Abstract : For this study, a bubbling fluidized bed biomass gasifier was operated with hot gas cleaning and bio‐syngas utilization in a high temperature solid oxide fuel cell (SOFC). The effect of internal tar reforming inside the anode‐supported SOFC was investigated.